Staphylococcus epidermidis and Staphylococcus aureus trigger different interleukin‐8 and intercellular adhesion molecule‐1 in lung cells: implications for inflammatory complications following neonatal sepsis. (5th August 2013) - Ivarsson, Mikael; Schollin, Jens; Björkqvist, Maria
Abstract: Aim: Staphylococci are a major contribution for neonatal sepsis, which is the main risk factor for bronchopulmonary dysplasia. This study investigated the expression of pro‐inflammatory mediators in endothelial and respiratory cells from newborns exposed to staphylococci. Methods: Human vascular endothelial cells and small airway epithelial cells were incubated with neonatal blood isolates of Staphylococcus epidermidis (n = 14) and Staphylococcus aureus (n = 14). The extracellular release of IL‐8, IL‐10, sICAM‐1, ICAM‐1 mRNA and the expression of membrane bound ICAM‐1 were assessed by ELISA, RT‐PCR and immunofluorescence microscopy. Results: Staphylococcus epidermidis induced higher levels of IL‐8 (mean 38.5 ng/mL) and ICAM‐1 mRNA (mean ratio 1.037) in the small airway epithelial cells than S. aureus (IL‐8 mean 22.2 ng/mL, p < 0.01 and ICAM‐1 mRNA mean ratio 0.715, p < 0.01). In the endothelial cells, ICAM‐1 remained more integrated in the cell membranes after exposure to S. epidermidis compared with S. aureus, which induced disintegration and release of soluble ICAM‐1 into the supernatants. Conclusion: Staphylococcus epidermidis induced a higher chemoattractive response than S . aureus . A persistent transmigration of granulocytes into the lung tissue in neonatal S. epidermidis sepsis might contribute to the development of bronchopulmonary dysplasia.